2020
DOI: 10.1371/journal.pone.0236351
|View full text |Cite
|
Sign up to set email alerts
|

Selection criteria for high-yielding and early-flowering bread wheat hybrids under heat stress

Abstract: Hybrid performance during wheat breeding can be improved by analyzing genetic distance (GD) among wheat genotypes and determining its correlation with heterosis. This study evaluated the GD between 16 wheat genotypes by using 60 simple sequence repeat (SSR) markers to classify them according to their relationships and select those with greater genetic diversity, evaluate the correlation of the SSR marker distance with heterotic performance and specific combining ability (SCA) for heat stress tolerance, and ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 68 publications
4
45
0
Order By: Relevance
“…Moreover, four crosses, i.e., WL8 × WT17, WL37 × WT17, WL8 × WT39, and WL37 × WT39, which displayed significantly positive SCA effects under both optimal and heat stress conditions for grain yield per plant, were derived from the parents with the same types of general combining ability effects (high x high) under these conditions. The prevalence of such crosses indicates the presence of non-additive genetic control of grain yield in wheat under optimal and heat stress conditions as suggested [29]. The presence of higher dominance variance than additive also confirms non-additive gene action for this trait under both optimal and stress conditions.…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, four crosses, i.e., WL8 × WT17, WL37 × WT17, WL8 × WT39, and WL37 × WT39, which displayed significantly positive SCA effects under both optimal and heat stress conditions for grain yield per plant, were derived from the parents with the same types of general combining ability effects (high x high) under these conditions. The prevalence of such crosses indicates the presence of non-additive genetic control of grain yield in wheat under optimal and heat stress conditions as suggested [29]. The presence of higher dominance variance than additive also confirms non-additive gene action for this trait under both optimal and stress conditions.…”
Section: Discussionmentioning
confidence: 55%
“…Multivariate analyses (SMLR and path coefficient) are effective instruments for understanding the relationship between interpretive traits for yield [ 60 , 61 ]. It has also been found that using simple correlation without regard to interactions between interpretive traits for yield may not be useful for finding successful breeding programs [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…SMLR had a coefficient of determination (R 2 ) of 0.886. Many investigators have used multivariate analyses [ 61 , 63 , 64 ]. Based on SMLR, we used path analysis to separate the five interpretive traits obtained by SMLR into the direct and indirect impacts for each trait.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the dominant source of calories and protein for most countries, giving it an important role in food security. The continuously increasing human population creates a need for continuous increases in grain yield, resulting in serious challenges for plant breeders to generate more varieties with higher productivity [ 1 , 2 ]. Increasing grain yield and tolerance to biotic and abiotic stress conditions are fundamental goals for the genetic improvement of wheat [ 3 ].…”
Section: Introductionmentioning
confidence: 99%